2013
DOI: 10.2478/intag-2013-0001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of particle size on physical and sensory attributes of mango pulp powder

Abstract: A b s t r a c t. The present investigation was aimed to observe the effect of particle size on physical, sensory and thermal properties of foam-mat dried mango pulp powder. Mango pulp of Dussehri variety was foam-mat dried using 3% egg white at 65°C. Dried foam-mats were pulverized and passed through a sieve shaker for obtaining three grades of powder with 50, 60, and 85 mesh size sieves. The particle size of these samples measured using laser diffraction particle size analyzer ranged from 191.26 to 296.19 µm.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 20 publications
(18 reference statements)
3
18
0
1
Order By: Relevance
“…As can be seen, a decrease in particle size caused an increase in lightness and a decrease in the greenness and yellowness ( Table 2). The significant effect of particle size on the L* component was also confirmed by other researches, e.g., Sharma et al (2013) who studied properties of mango pulp powders.…”
Section: Color Size and Morphology Of Pumpkin Seed Oil Powderssupporting
confidence: 70%
“…As can be seen, a decrease in particle size caused an increase in lightness and a decrease in the greenness and yellowness ( Table 2). The significant effect of particle size on the L* component was also confirmed by other researches, e.g., Sharma et al (2013) who studied properties of mango pulp powders.…”
Section: Color Size and Morphology Of Pumpkin Seed Oil Powderssupporting
confidence: 70%
“…The fine particles issued from the combination of drying, grinding, and sieving processes enable a better release of bioactive substances owing to their high specific surface area (Rosa, Barron, Gaiani, Dufour, & Micard, ; Zhao et al, ). Several recent studies have reported the link between particle size range of plant powders, bioactive ingredient contents, physicochemical properties, and functionalities (Becker et al, ; Sharma, Kadam, Chadha, Wilson, & Gupta, ; Zaiter, Becker, Karam, et al, ). With the increasing quantity and variety of powdered ingredients used in industry (Sharma et al, ), production of plant powders constitutes an important step for their valorization in various industrial sectors.…”
Section: Introductionmentioning
confidence: 99%
“…Application of suitable technological treatments ie agglomeration or coating, allows obtaining numerous profitable features of products from the point of view of food quality and safety, including especially stability during processing and storage (Dacanal and Menegalli, 2010;Sharma et al, 2013). Dairy-based powders constitute a large part of instant powders used in the food industry.…”
Section: Introductionmentioning
confidence: 99%